Med krvjo in skrbjo - Zaviršek, Darja (Socialno delo, 2009)
Social parenthood is a social relation, social cathegory, and a concept which due to changes in people's everyday life has gained scientific attention. The concept of social parenthood stands in opposition to the biological parenthood and challenges the assumption that parenthood refers to kinship.Parenthood hasnever been exclusively based on biological relations. Social parenthood refers to children and adults that are not related by blood. In Slovenia, parenthood is taken to equal consanguine relationas. Conversely, adults and children that are not biologically related are usually not considered to be inthe parent-children relationship. However, there is a growing number of families with a mixture of biological and social parenthood, often named "blended families", "adoptive families", "same-sex families", and families that use reproductive technology for reproduction. Social parenthood is a permanent, intimate relation between an adult and a child that is not based on blood ties but on social-emotional ones and includes the adult's economic responsibility for the child. For the child, parents are "important others" regardless of whether they are defined as such in legislation. Using an historical and ethnographic perspective, the author shows how consanguine relations in Europe gained such an important status in comparison to social ties between children and adults, and points out a continous demonising of non-blood parental ties that are still reflected in Slovenia family law.
Keywords: socialno starševstvo; sorodstvo; starševstvo; družinski zakonik